1999
DOI: 10.1177/089686089901900409
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Defense Using Icodextrin Or Glucose for Daytime Dwell in Ccpd Patients

Abstract: Objective To investigate peritoneal defense during icodextrin use in continuous cyclic peritoneal dialysis (CCPD). Design In an open, prospective, 2-year follow-up study, CCPD patients were randomized to either glucose (Glu) or icodextrin (Ico) for their long daytime dwell. Setting University hospital and teaching hospital. Patients Both established and patients new to CCPD were included. A life expectancy of more than 2 years, a stable clinical condition, and written informed consent were necessary before ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 23 publications
2
29
0
2
Order By: Relevance
“…aPDE was prepared by adding pooled human plasma from five donors to unused commercially available PD fluid at a final protein concentration of 1 μg/μL, mimicking the composition of PDE in the clinical setting . The resulting aPDE was then analyzed by 2DE in order to resolve the solubilized proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aPDE was prepared by adding pooled human plasma from five donors to unused commercially available PD fluid at a final protein concentration of 1 μg/μL, mimicking the composition of PDE in the clinical setting . The resulting aPDE was then analyzed by 2DE in order to resolve the solubilized proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, 500 mL of unused PDF was supplemented with 7.14 mL of human plasma (= 0.5 g of plasma protein) corresponding to a typical clinical protein concentration of 1 μg/μL . Spiking was performed with 180 μL of CP lysate (= 400 μg of CP), corresponding to a typical clinical peritoneal cell count of 1–2 cells per μL . The concentrations of the CP lysates used for spiking were between 2.2 and 2.5 μg/μL resulting in a negligible added volume in the range of 0.03% v/v.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed data of 1275 patients that included 677 who were treated by PD using icodextrin . Among 13 studies, five, three, and one were of patients treated with continuous ambulatory peritoneal dialysis (CAPD) , automated peritoneal dialysis (APD) [11,13,14], and continuous cycling peritoneal dialysis (CCPD) [15], respectively, and the remainder comprised combinations of the modalities. Two studies involved patients only with diabetes [16,17] and one of the other studies was limited to non-diabetic patients [18].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The design of five studies was openlabel and dropout rates were high in all of them. These results might also be biased and attenuated in relation to icodextrin because hypertonic 3.86% and 4.25% glucose PD solutions served as controls without restrictions in two trials [15,19].…”
Section: Peritoneal Ultrafiltrationmentioning
confidence: 99%
“…Several in vitro and ex vivo studies have suggested that icodextrin may offer improved peritoneal membrane biocompatibility compared with conventional glucosebased dialysates by virtue of decreased glucose exposure, iso-osmolarity and reduced carbonyl stress. [30][31][32][33][34][35][36][37][38] Shortterm clinical studies involving generally small numbers of patients have demonstrated that dialytic small solute clearances and peritoneal transport characteristics remain well-preserved on icodextrin therapy for up to 24 months of follow up. 5,13,14,20,37,39,40 Moreover, a prospective, open-label, randomized controlled trial of 38 CCPD patients in two centres showed that dialysate effluent concentrations of a variety of peritoneal membrane markers (CA125, interleukin-8, carboxyterminal propeptide of type I procollagen and aminoterminal propeptide of type III procollagen) did not differ between glucose-and icodextrin-treated patients over a 2-year period.…”
Section: Biocompatibilitymentioning
confidence: 99%